I believe you combine the first and last terms first because they have the same denominator
Answer:
SAS
Step-by-step explanation:
It would be r,o beacuse of the grid cordinates in the sentence
Answer:
f(x) = (x + 10)(x + 4)(x - 1)
Step-by-step explanation:
Given the zeros of a polynomial, say x = a and x = b, then
the factors are (x - a) and (x - b)
The polynomial is then the product of the factors
f(x) = (x - a)(x - b)
Here the zeros are x = - 10, x = - 4 and x = 1, thus the factors are
(x - (- 10)), (x - (- 4)) and (x - 1), that is
(x + 10), (x + 4) and (x - 1)
f(x) = (x + 10)(x + 4)(x - 1)